ANALISIS VARIABEL MAKROEKONOMI DALAM MEMPENGARUHI PENYERAPAN TENAGA KERJA DI PULAU JAWA - Vena Klarisa Irawati; Panji Kusuma Prasetyanto (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2022)
This study provides an overview of the effect of macroeconomic variables, namely the provincial minimum wage and domestic investment on employment. The combination of the use of time series data for the period 2016-2020 and cross section data from six provinces on the island of Java, namely Banten, West Java, DKI Jakarta, Central Java, Yogyakarta Yogyakarta, and East Java, is used by the authors in this study. In other words, this study uses panel data regression with the help of Eviews 10 software in its management. The results show that the provincial minimum wage has a significant positive effect on employment on the island of Java, domestic investment has a significant negative effect on employment on the island of Java, and together both have a significant effect on employment in the island of Java. Java in the research period. Thus, the macroeconomic variables in this study have a contribution in determining the absorption of labor on the island of Java.